2010
DOI: 10.5539/jas.v2n4p254
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Application and Residues of Plant Growth Regulators in the Fruit Sugarcane Grown in the Sub-Suitable Region

Abstract: In this paper, we used plant growth regulators, such as gibberellin and ethephon to treat fruit sugarcane Qiantang 5 respectively. The results show that the spraying of gibberellin on the plants with its concentration of 30g/year.667m 2 has positive effects on most agronomic characters, such as growth speed, plant height, valid stalks, brix, sucrose content and yield. The residue of gibberellin is 0.05mg/kg. However, ethephon has no positive effects on agronomic characters except the growth speed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…e number of millable stalks (stalk population) was not significantly affected by the ripener main effect as well as by its interactions (Tables 1 and Figure 3). Similar to the current result, Lu et al [36] also demonstrated the negligible effect of 2-chloroethylophsphonic acid on stalk population. In contrast, Abo El-Hamd et al [35] reported a significant reduction in stalk population due to 2-chloroethylphosphonic acid applied at a higher rate (1143 g ai ha − 1 ).…”
Section: Number Of Millable Stalkssupporting
confidence: 91%
“…e number of millable stalks (stalk population) was not significantly affected by the ripener main effect as well as by its interactions (Tables 1 and Figure 3). Similar to the current result, Lu et al [36] also demonstrated the negligible effect of 2-chloroethylophsphonic acid on stalk population. In contrast, Abo El-Hamd et al [35] reported a significant reduction in stalk population due to 2-chloroethylphosphonic acid applied at a higher rate (1143 g ai ha − 1 ).…”
Section: Number Of Millable Stalkssupporting
confidence: 91%
“…Overnight soaking of setts in 100 ppm ethrel solution along with spray of GA 3 @ 35 ppm at 90, 120 and 150 DAP exhibited the higher 0 brix (18.64), sucrose % (17.7) and CCS % (11.79) in all the three years of this study. Lu et al (2010) found that spraying of gibberellic acid on sugarcane plants with its concentration of 30 g/667 M 2 /year had positive effects on 0 brix value and sucrose percent as well.…”
Section: Yield and Quality Parametersmentioning
confidence: 98%
“…We selected 45m/s [6]. To ensure the clearance between moving and stationary knives around 1mm, while the rotor rotation process, it should minimize the angle between the rotation axis and the knife edge line [7]. The sliding-cutting angle and setting angle are installed both 30°, to reduce power consumption.…”
Section: Design and Calculation Of Cutting And Screening Mechanismsmentioning
confidence: 99%